Work–life prevalence of self-reported occupational injuries in mothers of a birth cohort. Issue 2 (3rd April 2022) - Amaro, Joana; Queiroga, Ana Catarina; Amaro, João; Mehlum, Ingrid Sivesind; Lucas, Raquel
Abstract : Purpose . This study investigated self-reported occupational injuries among mothers in a large birth cohort study and the relation of their characteristics to different injury outcomes: occurrence, severity, temporal proximity and recurrence. Methods . We asked 4338 women whether they had been in 'an accident at work, even if it did not require medical treatment', and the number of accidents throughout their working life, type of injury and whether it occurred within the last 12 months. Results . Over one-fifth (21.8%) of working-age mothers reported having at least one occupational injury throughout their working life. Wounds and superficial injuries were the most frequently reported types of occupational injuries (11.0%), followed by dislocated bones and joints, sprains and strains (10.7%). Women who reported a history of occupational injuries also had a higher likelihood of reporting a work-related health problem (adjusted odds ratio [OR] = 2.64; 95% confidence interval [CI] [2.27, 3.07]) and of having a partner who also reported an occupational injury throughout their working life (adjusted OR = 1.86; 95% CI [1.33, 2.62]). Associations remained fairly stable across all outcomes. Conclusions . Our findings point towards a broadened understanding of occupational injury consequences and research focusing on family-level factors that account for the embeddedness of workers in households.